KINERJA APARATUR DESA DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT DI DESA PETANI KECAMATAN MANDAU KABUPATEN BENGKALIS - Michellia Agustin; M Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The issue of service to the community is always prominent in the affairs of public service, are registrasion of identity card, card of family, and ecextra. The existence of public complainsh tasksthat slow, working hours of the apparatur does not comply with the rules made public difficulty in optaining one.The research is focused to problem of how performance of village institution in give service to public. And what are the factors that influence the task of institution.The research it’s done in Petani village of Mandau subdistrict Bengkalis regency, and the research is done by quantitative descriptive approach.The result showed that the work ethic that is in the staff is looking for money, the status of the staff is as workers but it’s role is not in accordance with the devision of labor, socialization received staff of government is not going well, there is a control to village institution and it didn’t happen norm infraction and that values. And punishment that valid in the office is not effective for the institution.The keyword: performance, village institution, ethos work